PENGARUH MOTIVASI DAN INSENTIF TERHADAP KINERJA KARYAWAN DISTRIBUTION CENTER PT. INDOMARCO PRISMATAMA CABANG SURABAYA - EMMYWATI EMMYWATI (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
Motivation is one that raises the spirit or drive to work (Anoraga, 2010). Motivation questioned how to encourage morale so that they are willing to work hard, especially to the subordinates or followers so that they would work hard to provide all the capabilities and skills to realize the goal of the Vendor (Hasibuan, 2010). Issue of motivation is a major problem that occurs in every organization, because the motivation in an organization has an influence on the effectiveness of the organization. If a high work motivation is most likely the result of his work will be satisfactory. Another way to improve the performance of employees is by providing incentives to employee. Incentives are additional salary received by the employee in retaliation for their work as carrying out work pursuant to or higher than the standards that have been set. Providing incentives for employees are as a driver who can motivate employees to work harder effectively. Incentives are closely linked to the performance of the employee. There are tradeoffs in both directions between incentives to performance. Incentives are given due to a good performance and is given to further improve the performance again in the future. This research was conducted by using a quantitative approach, the research focused on testing the hypothesis by means of statistical methods of analysis and produce conclusions that can be generalized. Sample in this research is the employee's Distribution Center PT. Indomarco Prismatama. Sampling method used in this study and nomogram table Krejcie Harry King. Test equipment used is the technique of multiple linear regression analysis with SPSS 18.0 software. After testing the above hypothesis, the obtained results of the F test that variable motivation and incentive variable simultaneously significant positive effect on performance. T Test results also showed that the variables of motivation and incentive variables partially significant positive effect on performance.